The Cambridge companion to Dante (Cambridge companions to literature, ,, 1993)
This book provides an introduction to Dante that is at once accessible and challenging. Fifteen essays provide background information and up-to-date critical perspectives on Dante's life and work, focusing on areas of central importance. Three essays introduce the three canticles of the Divine Comedy, and others explore the literary, intellectual and historical background to Dante's writings, his other works and his reception in the commentary tradition and in literature in English. The book also includes a chronological table and suggestions for further reading.
Life of Dante / Giuseppe Mazzotta , Dante and the lyric past / Teodolinda Barolini , Approaching the Vita nuova / Robert Pogue Harrison , The unfinished author : Dante's rhetoric of authority in Convivio and De vulgari eloquentia / Albert Russell Ascoli , Dante and the empire / Charles Till Davis , Dante and Florence / John M. Najemy , Dante and the classical poets / Kevin Brownlee , Dante and the bible / Peter S. Hawkins , The theology of Dante / Christopher Ryan , A poetics of chaos and harmony / Joan Ferrante , Introduction to Inferno / John Freccero , Introduction to Purgatorio / Jeffrey T. Schnapp , "Shadowy prefaces" : an introduction to Paradiso / Rachel Jacoff , Dante and his commentators / Robert Hollander , Dante in English / David Wallace.

The Cambridge companion to John Donne (Cambridge companions to literature, ,, 2006)
Description Not Provided
Donne's life: a sketch / Jonathan F.S. Post , Text of Donne's writings / Ted-Larry Pebworth , Social context and nature of Donne's writings: occasional verse and letters / Arthur F. Marotti , Literary contexts: predecessors and contemporaries / Andrew Hadfield , Donne's religious world / Alison Shell and Arnold Hunt , Donne's political world / Tom Cain , Reading and rereading Donne's poetry / Judith Scherer Herz , Satirical writing: Donne in shadows / Annabel Patterson , Erotic poetry / Achsah Guibbory , Devotional writing / Helen Wilcox , Donne as preacher / Peter McCullough , Donne's language: the conditions of communication / Lynne Magnusson , Gender matters: the women in Donne's poems / Ilona Bell , Facing death / Ramie Targoff , Donne's afterlife / Dayton Haskin , Feeling thought: Donne and the embodied mind / A.S. Byatt.